Day fines in Europe: assessing income-based sanctions in criminal justice systems - Kantorowicz-Reznichenko, Elena; Faure, Michael G. (Cambridge University Press, 2021)
Day fines, as a pecuniary sanction, have a great potential to reduce inequality in the criminal sentencing system, as they impose the same relative punishment on all offenders irrespective of their income. Furthermore, with correct implementation, they can constitute an alternative sanction to the more repressive and not always efficient short-term prison sentences. Finally, by independently expressing in the sentence the severity and the income of the offender, day fines can increase uniformity and transparency of sentencing. Having this in mind, almost half of the European Union countries have adopted day fines in their criminal justice system. For the first time, this book makes their findings accessible to a wider international audience. Aimed at scholars, policy makers and criminal law practitioners, it provides an opportunity to learn about the theoretical advantages, the practical challenges, the successes and failures, and ways to improve.